Pertanggung Jawaban Penyidik Kepolisian Terhadap Kasus Salah Tangkap - Andiani Oktavia Safitri (Universitas 45 Surabaya, 2024)
The case of wrongful arrest is not a new story in the world of Indonesian law. Wrongful arrest or error in person are people who individually or collectively suffer physically or mentally as a result of procedural errors or errors in the investigation or detention process carried out by authorized law enforcement officials or similar. So it can be concluded that the victims of wrongful arrest were caused by errors in the investigation or detention process. Police officers in carrying out their duties must prioritize the principle of presumption of innocence to avoid mistakes in making arrests. The National Police's mistakes in carrying out arrests include disciplinary violations and violations of the Indonesian Police Professional Code of Ethics. Considering that the consequences of a wrongful arrest case are very large as described above, especially for the victim, it is the obligation of the National Police investigator to be accountable for his actions. The Criminal Procedure Code explains the rights obtained by victims of wrongful arrest, namely compensation as regulated in Article 95 paragraph (1) of the Criminal Procedure Code which states that suspects, defendants or convicts have the right to claim compensation for being arrested, detained, prosecuted and tried or subjected to other actions without reasons based on law or because of a mistake regarding the person or the law applied, and receive rehabilitation as regulated in article 97 of the Criminal Procedure Code.